Immunopathogenesis of COVID-19: Summary and Possible Interventions - Jacques, Francois Henri; Apedaile, Erik (Frontiers in Immunology, 2020)
Since the onset of the COVID-19 pandemic in the fall of 2019 over 4 million people have been infected and over 280,000 have died (1). Information about the COVID-19 SARS-CoV2 virus is evolving rapidly. At this time there are no interventions proven to be effective for cases infected with SARS-CoV2COVID-19. Current knowledge about the clinical and laboratory manifestations of COVID-19 infection is reviewed and combined with knowledge about the immunopathogenic mechanisms of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV1) and Middle East Respiratory Syndrome (MERS) to formulate theories and suggest possible therapeutic interventions. SARS-CoV2 COVID-19 immunopathogenic mechanisms vary from immunosuppression that initially enables viral escape to a hyperinflammatory immune response. Ultimately therapeutic intervention will be phase dependent